UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIALMELALUI PENERAPAN METODE LATIHANSISWA KELAS II SD NEGERI 010 BANJAR PANJANGKECAMATAN KERUMUTAN - Sri Heruwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low social studies (IPS) learning outcomes of second-grade students at SD Negeri 010 Banjar Panjang, Kerumutan District. Of the 20 students, only 10 students (50.00%) achieved the minimum mastery criterion (KKM). The purpose of this study was to improve IPS learning outcomes through the implementation of the training method. This research was a classroom action research conducted in two cycles. The data focused on improving learning mastery and students’ IPS learning outcomes. The results showed that after the implementation of the training method, learning outcomes and student mastery increased. Based on the preliminary data, 10 students (50%) achieved mastery, which increased to 14 students (70%) in the first cycle and further increased to 16 students (80%) in the second cycle. In addition, students’ IPS learning outcomes also improved, with the average score increasing from 55 in the preliminary data to 60 in the first cycle and to 64 in the second cycle.